Succinate as a metabolic–signaling dual-function hub in skeletal muscle: linking exercise adaptation to myopathic dysfunction - Juncheng Si; Haodong Tian; Mingkun Guo; Yongxia Lin; Yongshan Gong; Yang Wang; Li Peng (Molecular Biology Reports, 2026)

Molecular Mechanisms of Weak Electric Field-Regulated Nitrate Transport Mediated by Nrt Protein - Wei Guo; Haodong Liu; Feng Lin; Lei Gao; Guangcan Zhu (Environmental Research, 2026)

Model test study of polyurethane grouting repair for gas pipelines in mining subsidence areas - Du Zibo; Tian Haodong; Ma Zhanguo; Li Lin; Zhang Jingwei; Zhou Chuang (Tunnelling and Underground Space Technology, 2026)

Semaglutide treatment reverses HFD induced hippocampal microglia activation and improves cognitive dysfunction - Haodong Gong; Junlu Liu; Yihan Wang; Xufan Lin; Guangsen Wu; Yichao Ou; Mingfeng Zhou; le Yang; Junxiang Peng; Xinyun Ye; Yongjia Wang; Fei Xu; et al. (Tissue and Cell, 2026)

Synergistic atomic-level anchoring and pore engineering of cobalt-nitrogen-carbon for anti-fouling and robust capacitive deionization - Huakun Pan; Haodong Zhang; Xinxi Teng; Yang Fan; Yaming Wang; Lin Li; Guisong Zhang; Meiling Liu; Haiou Song; Aimin Li; Shupeng Zhang (Chemical Engineering Journal, 2026)

Contrasting tolerance and nutritional responses to exogenous GABA in two marine diatoms - Yanyu Wang; Ningxin Yan; Qiaoqi Luo; Yuandi Zhang; Haodong Luo; Xin Lin (Algae, 2026)
While γ-aminobutyric acid (GABA) promotes nutrient accumulation in green microalgae, its effects on marine diatoms—critical aquaculture feed—remain understudied. Understanding the physiological response of diatoms to exogenous GABA is vital for optimizing high-quality feed production. In this study, we investigated the impact of GABA on diatom growth, photosynthetic performance, proximate composition (lipids, proteins, carbohydrates, and fatty acids), and oxidative stress markers of two commonly used feed diatoms Phaeodactylum tricornutum and Chaetoceros muelleri. GABA effects were species-specific: low doses (0.2–1.0 pmol cell−1) inhibited P. tricornutum at the exponential onset, while C. muelleri remained resilient to higher doses (1.5–16.2 pmol cell−1). Notably, this resilience in C. muelleri shifted to growth promotion when GABA was applied at the late stage, demonstrating clear stage-dependency. In P. tricornutum, supplementation with 0.2–1.0 pmol cell−1 GABA triggered a significant accumulation of cellular carbohydrates, proteins, and lipids accompanied by a broad-spectrum increase in various cellular fatty acid concentrations including polyunsaturated fatty acids (PUFAs), such as eicosapentaenoic acid and docosahexaenoic acid. Notably, 1.0 pmol cell−1 GABA induced a three-fold increase in carbohydrate and lipid levels over the control. GABA triggered significant oxidative stress and photosynthetic inhibition in P. tricornutum in a dose-dependent manner, while C. muelleri exhibited high physiological tolerance with no marked changes in reactive oxygen species, superoxide dismutase, or photosynthetic efficiency. A two-stage cultivation strategy involving initial biomass maximization and subsequent GABA-induced nutrient enrichment can be effectively utilized to biofortify P. tricornutum for use as aquaculture feed.

Endogenous piezoelectric-triboelectric mechanism enables enhanced sensitivity and voltage output of FPI/ANF composite films - Xu Zhang; Haodong Lin; Bilin Zhang; Kai Yang; Yachuan Miao; Fei Liu; Jianwei Li (Chemical Engineering Journal, 2026)

Prospective ex-ante life cycle assessment of an emerging resource recovery solution based on food waste - Haodong Lin; Isabela Butnar; Aiduan Borrion (The International Journal of Life Cycle Assessment, 2026)
Purpose Emerging technologies facilitate the circular economy transition by converting waste into value-added products. Environmental assessments of these technologies are increasingly gaining attention; however, scaling up remains a major challenge, leading to significant data gaps. To address this issue, this study applied an ex-ante LCA to a resource recovery solution integrated with an emerging technology, comparing three upscaling approaches: simple extrapolation, process engineering modelling, and approximation. Methods The ex-ante LCA was conducted in accordance with ISO 14,040 and 14,044 standards to evaluate the environmental impacts of the resource recovery solution, integrating an emerging digestate valorisation technology into a conventional anaerobic digestion plant. Life cycle inventories were compiled from a UK anaerobic digestion plant and the upscaled technology, applying the three upscaling approaches. Four near-future scenarios were developed: a business-as-usual case and three scenarios based on the respective upscaling methods. Five impact categories relevant to digestate production and management were evaluated: climate change, fine particulate matter formation, terrestrial acidification, fossil resource scarcity, and water use. Additionally, long-term future scenarios were established by adopting projected future background data, considering shared socioeconomic pathway 2, representing a middle-of-the-road development trajectory. Results and discussions Results show that, compared to the business-as-usual case, the resource recovery solution reduced more than 46% impacts in climate change, terrestrial acidification, and water use, primarily due to the avoided digestate storage and using recovered water. However, fine particulate matter formation and fossil resource scarcity impacts vary across upscaling methods. The process engineering modelling method demonstrated the best overall environmental performance, followed by approximation and simple extrapolation approaches. The long-term future scenario confirmed potential for improvements across all selected impact categories by 2050. Sensitivity analysis identified key parameters, including emission factors, recovery efficiencies, economic values of products, and upscaling factor. Conclusions This study applied ex‑ante LCA to assess the environmental impacts of a resource recovery solution and compared three upscaling methods to examine their influence on results. The findings underscore the importance of method selection, comprehensive impact assessment, and high‑quality data. Future work should include uncertainty and broader sustainability analysis. Overall, the study advances ex‑ante LCA by demonstrating how multiple upscaling approaches can address data gaps in bio‑waste resource‑recovery technologies and support early decision‑making in the anaerobic digestion sector.

Purifying ⁶⁰Co-containing low-level radioactive wastewater via electro-deionization with zirconium phosphate ion-exchange resins - Jinzheng Yuan; Haodong Jiang; Jinghao Guo; Hanzhi Wang; Guoyu Wen; Manuel César Martí-Calatayud; Jueyin Gong; Yuanhang Wang; Li Lin; Feng Luo; Tao Luo; Xinlong Wang (Journal of Hazardous Materials, 2026)

From plant optimization to economy-wide impacts: A techno-economic and environmentally extended input-output framework for green hydrogen deployment in cement - Sobit Sapkota; Anup Paudel; Aiduan Borrion; Haodong Lin; Jun-Ki Choi (Journal of Cleaner Production, 2026)

A multi-component recycling strategy for photovoltaic waste: Co-recovering silicon and PVDF into Ag–F reinforced Si/C anodes - Yihao Li; Yiqing Chen; Xiaojiao Zhang; Yaoguang Guo; Shuai Chen; Jie Yang; Tie Lin; Haodong Ran; Yang Zhang; Qin Xu; Yanlin Wu; Hao Yuan; et al. (Resources, Conservation and Recycling, 2026)

Valorisation of anaerobic digestate: Environmental life cycle assessment of anaerobic digestate value chain in the UK with a digestate treatment technology - Haodong Lin; Joris Šimaitis; Mairi J. Black; Aiduan Borrion (Journal of Cleaner Production, 2026)

A multiscale perspective on the occurrence, transport mechanisms, and molecular interactions of heavy metals in contaminated soils - Lin Mu; Fusheng Zha; Hua Guo; Mrunal Bokade; Sharad Pandey; Devendra Narain Singh; Qiao Wang; Tianyang Chen; Haodong Tai; Peifu Cai; Kai Huang; Huaxiang Yan (Environmental Research, 2026)

Adjuvant-metal-ion-chelating PTEN mRNA with cell-membrane-coating augments the immune sensitivity for precise cancer immunotherapy - Mengyu Guo; Jin-Cheng Guo; Haodong Yao; Fene Gao; Lina Zhao; Lu Cai; Xuan Fan; Lin Bao; Xin Li; Xiaoyu Zhang; Mingdi Hu; Jie Mei; et al. (Science Bulletin, 2026)

Modeling of industrial biomass fluidized bed gasification system and optimization of operating conditions - Haodong Fan; Han Zhang; Geng Li; Xiong Zhang; Zixue Luo; Lin Huang; Shihong Zhang (Biomass and Bioenergy, 2026)

Enhanced El Niño–Southern Oscillation impact on Somali jet under greenhouse warming - Haodong Wang; Tao Geng; Wenju Cai; Shuo Wu; Xiaopei Lin (Climate Dynamics, 2026)

Effects of MS-222 on the physiological and biochemical response, histomorphology, gut microbiota, and flesh quality in largemouth bass (Micropterus salmoides) - Ping Gao; Rimeng Chen; ShanShan Lin; Haodong Yu; Xuezhen Zhang (Fish Physiology and Biochemistry, 2025)

In-situ growth of TiO2 nanoparticles on MXene to construct 3D copper-based catalyst for methanol steam reforming - Rensheng Song; Guangbo Zhou; Minghui Lian; Haodong Chen; Lei Wang; Jinxiao Li; Chunhua Yang; Xinyu Lin; Liwei Pan (Fuel, 2025)

Cyclic Response and Bending Behavior of Lattice-Shaped Diaphragm Wall Foundations for Cross-Sea Bridges: A Follow-Up Laboratory Study - Jiujiang Wu; Lin Xiao; Ting Yang; Haodong Hu; Sirui Pan (Geotechnical and Geological Engineering, 2025)

Integrating mass defect filtering and targeted molecular networking for foodomics research: A case study of Magnolia officinalis cortex - Qi Wang; Haodong Zhu; Hong Zhou; Congwei Yu; Xupeng Tong; Xinya Zhang; Aijing Li; Pei Lin; Xinsheng Yao; Keshen Li; Liangliang He; Zhihong Yao (Food Research International, 2025)

Development and validation of a prediction model for the depressive symptom risk in commercial airline pilots - Jie Zhang; Xuhua Chen; Lin Zhang; Haodong Qi; Erliang Zhang; Minzhi Chen; Yiran Wang; Yunfei Li; Yan Chen; Qingqing Duan; Feng Shi; Linlin Wang; et al. (EPMA Journal, 2025)

Biogas utilisation – Life cycle assessment of enabling technology for transport biomethane - UK case study, Bore Hill farm Biodigester - Haodong Lin; Mairi J. Black; Olivia Lin; Thomas Minter; Aiduan Borrion (Biomass and Bioenergy, 2024)

Nutrient-rich sediment promotes, while fertile water inhibits the growth of the submerged macrophyte Vallisneria denseserrulata: implications for shallow lake restoration - Haodong Chen; Liu Yang; Zhenmei Lin; Sipeng Yao; Hu He; Xiaolong Huang; Zhengwen Liu; Erik Jeppesen; Jinlei Yu (Hydrobiologia, 2024)

Water availability may not restrict the implementation of carbon capture utilization and storage technology: Evidence from China's electric power sector - Haodong Lv; Xi Lu; Lin Yang; Ning Wei; Yiming Li; Xian Zhang (Resources, Conservation and Recycling, 2024)

Time development of live-bed scour around an offshore-wind monopile under large current–wave ratio - Xin Wang; Jing Yuan; Xu Qiu; Haodong Huang; Peng Lin; Xin Liu; Hao Hu (Coastal Engineering, 2024)

Life cycle assessment of baby leaf spinach: Reduction of waste through interventions in growing treatments and packaging - Haodong Lin; Mairi J. Black; Lael Walsh; Francesco Saverio Giordano; Aiduan Borrion (Journal of Cleaner Production, 2024)

3D/2D MnO/MXene heterostructure with high efficiency for adsorbing uranium - Chao Zhang; Yi Wang; Yi-Lin Liu; Qingming Zeng; Yanjun Wen; Lulin Guo; Haodong Chen; Xinyi Xie; Qingyi Zeng (Chemical Engineering Journal, 2024)

Implications of multi-stage deformation on the differential preservation of Lower Paleozoic shale gas in tectonically complex regions: New structural and kinematic constraints from the Upper Yangtze Platform, South China - Haodong Hou; Wei Yang; Wei Du; Xia Feng; Zhenxue Jiang; Fulun Shi; Ruiqin Lin; Yisong Wang; Daquan Zhang; Yi Chen; Zhao Sun; Fuping Zhao (Marine and Petroleum Geology, 2024)

An electroconductive hydrogel with injectable and self-healing properties accelerates peripheral nerve regeneration and motor functional recovery - Zhenwei Yi; Fangke Zhan; Yijia Chen; Ran Zhang; Haodong Lin; Liming Zhao (Chemical Engineering Journal, 2023)

Synergistically adsorbing and reducing Uranium from water by a novel nano zero-valent copper/MXene 0D/2D nanocomposite - Yi-Lin Liu; Chao Zhang; Lulin Guo; Qingming Zeng; Rongzhong Wang; Haodong Chen; Qingyan Zhang; Qingyi Zeng (Water Research, 2023)

Improved viability of probiotics encapsulated by layer-by-layer assembly using zein nanoparticles and pectin - Bu Liu; Jielun Hu; Haodong Yao; Lin Zhang; Huan Liu (Food Hydrocolloids, 2023)

Study on effect of equivalent initial water content on dredged sludge treated by VP-FSCM - Xiaoya Bian; Haodong Yang; Kun Duan; Rongjun Zhang; Lin Wu (Transportation Geotechnics, 2023)

Engineered metal coverage of anode catalyst layer enhancing cell reversal tolerance for proton exchange membrane fuel cells - Zheng Li; Haodong Huang; Yameng Wang; Yongbiao Mu; Yuting Jiang; Qing Zhang; Tianshou Zhao; Lin Zeng (Chemical Engineering Journal, 2023)

A visible and near-infrared light dual-responsive PEC immunosensor for archaeological silk microtrace detection based on in situ growth of Ag2S on ZnO-MXene nanocomposites - Qingqing Zhou; Yong Liu; Lin Wang; Kun Wang; Haodong Chen; Hailing Zheng; Yang Zhou; Zhiwen Hu; Zhiqin Peng; Junmin Wan; Bing Wang (Chemical Engineering Journal, 2023)

The evolution and determinants of Chinese inter-provincial green development efficiency: an MCSE-DEA-Tobit-based perspective - Lin Yang; Zhanxin Ma; Jie Yin; Yiming Li; Haodong Lv (Environmental Science and Pollution Research, 2023)

Corrosion Mechanism of 5083 Aluminum Alloy in Seawater Containing Phosphate - Jiaming Wang; Haodong Yang; Min Du; Jian Hou; Wenshan Peng; Cunguo Lin (Journal of Ocean University of China, 2021)

Whether China made efforts to decouple economic growth from CO2 emissions?-Production vs consumption perspective - Lin Yang; Yuantao Yang; Haodong Lv; Dong Wang (Environmental Science and Pollution Research, 2020)

Pros and Cons: Autophagy in Acute Spinal Cord Injury - Zheng Li; Tianshi Chen; Yuanwu Cao; Xiaoxing Jiang; Haodong Lin; Jian Zhang; Zixian Chen (Neuroscience Bulletin, 2019)

Position-domain integrity risk-based ambiguity validation for the integer bootstrap estimator - Liang Li; Haodong Shi; Chun Jia; Jianhua Cheng; Hui Li; Lin Zhao (GPS Solutions, 2018)

Altered Expression of Inducible Nitric Oxide Synthase After Sciatic Nerve Injury in Rat - Haodong Lin; Chunlin Hou; Desong Chen (Cell Biochemistry and Biophysics, 2011)